Carrying capacity assessment of a developing agricultural watershed using integrated modelling approach - Chhuon, Kong
The utilization of natural resources, such as water and land, is closely interlinked with sustainable development goals. The resources within a watershed should be utilized for the benefit of local community and in harmony with the environment. The carrying capacity of available water resources was assessed to meet the demands for people, agriculture, energy development and environmental protection within the watershed approach. This was applied to a watershed in Cambodia, Prek Te basin, a tributary of Mekong River. Prek Te is a developing agricultural watershed with increasing concern for land and water resource degradation. It is essential therefore to assess watershed carrying capacity in terms of water quantity and quality in order to assure water security, economic development and environmental protection in accordance with the government's investment road map. This study utilized an integrated modeling approach to spatially and temporally extrapolate available field survey and monitoring data and to provide a platform for the analysis of watershed management scenarios. A socio-economic survey was carried out to gather information on livelihood, agricultural practices, water resources use and environmental concerns of local people. These were accordingly incorporated into the model setup and scenario selection procedure. The soil and water assessment tool (SWAT) which characterizes basin hydrology with water quality and the river basin management model (MODSIM) which provides a decision support system for water allocation optimization, were used in this study. The models were calibrated and validated within the acceptable level of accuracy to assure reliability (R2=0.86 and NSE=0.78 for discharge, R2=0.85 and NSE=0.77 for nitrate, R2=0.70 and NSE=0.56 for phosphorus). The models were used to investigate catchment hydrology and water allocation for hydropower and irrigation system. A simulation of the water quality impact and agriculture productivity for different scenarios was also done. The study investigated soil erosion response to changes in land cover and identified management practices (MPs) for soil erosion control. All of which were defined within the carrying capacity for quality and quality of Prek Te River.